Acetyl-CoA production by encapsulated pyruvate ferredoxin oxidoreductase in alginate hydrogels. (March 2017) - Takenaka, Makoto; Yoon, Ki-Seok; Matsumoto, Takahiro; Ogo, Seiji
Graphical abstract: Highlights: PFOR was anaerobically purified from Citrobacter sp. S-77. Ceramic hydroxyapatite acted as a stable matrix of PFORS77 in alginate hydrogels. Efficient acetyl-CoA production by the immobilized PFOR was achieved. The PFORS77 -HA hydrogels had remarkable reusability under anaerobic conditions. Abstract: Pyruvate ferredoxin oxidoreductase from Citrobacter sp. S-77 (PFORS77 ) was purified in order to develop a method for acetyl-CoA production. Although the purified PFORS77 showed high O2 -sensitivity, the activity could be remarkably stabilized in anaerobic conditions. PFORS77 was effectively immobilized on ceramic hydroxyapatite (PFORS77 -HA) with an efficiency of more than 96%, however, after encapsulation of PFORS77 -HA in alginate, the rate of catalytic acetyl-CoA production was highly reduced to 36% when compared to that of the free enzyme. However, the operational stability of the PFORS77 -HA in alginate hydrogels was remarkable, retaining over 68% initial activity even after ten repeated cycles. The results suggested that the PFORS77 -HA hydrogels have a high potential for biotechnological application.